Early palliative care decision is associated with reduced end-of-life healthcare utilization in patients with esophageal and gastric cancer - Kitti, Pauliina; Nåhls, Nelli-Sofia; Koivusalo, Sofia; Leskelä, Riikka-Leena; Anttonen, Anu; Saarto, Tiina; Akrén, Outi; Carpén, Timo (Journal of Gastrointestinal Oncology, 2026)
Background: Patients with esophageal and gastric cancer have a poor prognosis and high symptom burden. The timing of palliative care decision (PC decision) i.e., discontinuing anticancer treatments and focusing on palliative care, can influence the utilization of healthcare resources, such as hospitalizations and emergency department (ED) visits, at the end of life. The aim of this study was to evaluate how the timing of the PC decision affects hospitalizations and ED visits during the last month of life.Methods: The retrospective study cohort (n=233) included all patients with esophageal or gastric cancer, treated at the Comprehensive Cancer Center of Helsinki University Hospital, during 2017–2018, and died by the end of 2018. The data on acute healthcare utilization in secondary or tertiary care were extracted from the hospital database. We compared healthcare utilization (ED visits and hospitalizations) based on the timing of the PC decision: early (>30 days before death), vs. no/late (≤30 days before death).Results: The PC decision was made for 184 patients (79%): in 104 (47%) the decision was early, in 80 (34%) it was late and 49 patients (21%) had no PC decision before death. Median time from PC decision to death was 87.5 days in the early PC decision group vs. 13.5 days in the no/late group, P